Moral emotions as antecedents of political attitudes - Petrescu, D; Dragos C. Petrescu (2013)
The main objective of this thesis was to investigate the proposition that moral emotions act as antecedents of political attitudes. My approach (Chapter 1) stems from moral foundations theory, which proposes that liberals and conservatives have different moral values (Graham, Haidt, & Nosek, 2009). Chapter 2 presents Study 1, an experimental test of the hypothesis that induced disgust leads participants to adopt more left-wing economic attitudes in comparison to a control condition (sadness). Results supported this hypothesis. Chapter 3 reviews emotion-regulation theories, and presents Study 2, which investigated whether emotion-regulation strategies, disgust sensitivity (DS-R), and private body consciousness (PBC) moderate the effects found in Study 1. As predicted, disgust led to more left-wing economic attitudes, but this was only the case for high-PBC and high-DS-R participants. Chapter 4 presents Study 3, which replicated Study 2, and showed dissociations between the effects of disgust on economic and social attitudes. Chapter 5 presents a cross-sectional investigation (Study 4) that tested for associations between the predisposition to experience disgust and both social and economic attitudes. As predicted, core disgust and pathogen disgust were associated with left-wing economic attitudes and these effects applied only to British participants, and not non-British participants. Chapter 6 presents Study 5 – an experiment investigating the relationship between disgust and prejudiced attitudes towards outgroups. Induced disgust led to more prejudiced attitudes towards a novel group than both sadness and neutral emotion. Chapter 7 is focused on two self-conscious moral emotions: guilt and shame. Study 6, presented in this chapter, found a positive association between guilt proneness and left-wing economic attitudes, and a relationship between shame proneness and social-conservative attitudes. Study 7 failed to reveal causal relationships between incidental guilt and shame and political attitudes. Chapter 8 presents the general discussion addressing limitations, implications, and future research directions.